2009
DOI: 10.1002/adfm.200900402
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐By‐Layer Dendritic Growth of Hyperbranched Thin Films for Surface Sol–Gel Syntheses of Conformal, Functional, Nanocrystalline Oxide Coatings on Complex 3D (Bio)silica Templates

Abstract: Here, a straightforward and general method for the rapid dendritic amplification of accessible surface functional groups on hydroxylated surfaces is described, with focus on its application to 3D biomineral surfaces. Reaction of hydroxyl‐bearing silica surfaces with an aminosilane, followed by alternating exposure to a dipentaerythritol‐derived polyacrylate solution and a polyamine solution, allows the rapid, layer‐by‐layer (LBL) build‐up of hyperbranched polyamine/polyacrylate thin films. Characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…Magnetite‐coated diatom frustules were synthesized in two different ways: Pre‐fabricated, dopamine‐modified magnetite NPs were attached to the diatom biosilica After the layer‐by‐layer formation of polyamine/polyacrylate thin films, iron oxide was deposited by a sol–gel process, which was converted into nanocrystalline magnetite by thermal treatment …”
Section: Functionalization Of Diatom Biosilica For Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetite‐coated diatom frustules were synthesized in two different ways: Pre‐fabricated, dopamine‐modified magnetite NPs were attached to the diatom biosilica After the layer‐by‐layer formation of polyamine/polyacrylate thin films, iron oxide was deposited by a sol–gel process, which was converted into nanocrystalline magnetite by thermal treatment …”
Section: Functionalization Of Diatom Biosilica For Nanotechnologymentioning
confidence: 99%
“…The obtained materials were effective as drug carriers and in the adsorption of arsenic from aqueous solution in a flow‐through system . Furthermore, it was demonstrated that magnetite NP‐coated diatom frustules loaded with small drug molecules could be delivered to tumors in vivo using external magnetic fields …”
Section: Functionalization Of Diatom Biosilica For Nanotechnologymentioning
confidence: 99%
“…Amine-functionalized polymers and small molecules have also been used in combination with reactive building blocks bearing isocyanate [81,82], dichlorophosphazene [83], acrylate [84][85][86]147], alkyl halide [87,88], epoxide [89], or aldehyde groups [90][91][92][93][94][95][96][97][98] to fabricate covalent LbL films cross-linked with urea [81,82], phosphazene [83], amino-ester [84][85][86]147], alkyl amine [84][85][86][87][88], or Schiff base [90][91][92][93][94][95][96][97][98] (imine) linkages. Approaches based on reactions between amine-and aldehyde-functionalized components (to form imine or Schiff base linkages) have been particularly well studied because of the relatively fast and mild (aqueous) nature of these reactions, which also permits reactive immobilization of biomacromolecular agents such as proteins into cross-linked multilayers.…”
Section: Other Reactions and Other Approachesmentioning
confidence: 99%
“…While in those cases it was necessary to introduce additional degradable functionality into polymer backbones or side-chains (because triazole linkages themselves are not readily degradable), the covalent Schiff-base linkages formed during assembly are reversible. Examples of reactive assembly based on the conjugate addition of primary amines to acrylate groups also inherently provide LbL routes to films containing ester-functionalized cross-links [84][85][86]147]. This approach could, thus, also provide a basis for the design of cross-linked multilayers that degrade in aqueous environments (e.g., by hydrolysis of ester functionality) and open the door to additional applications of these materials in biomedical contexts.…”
Section: Other Reactions and Other Approachesmentioning
confidence: 99%
“…There are estimated to be between 10 000-100 000 species of diatom, each with their unique intricate frustule. 13 The complexity and the precision with which the frustule is synthesized, at both the micro-and nano-scale, has attracted attention from many disciplines interested in the production of nanostructured materials, 14 with proposed applications in catalysis, 15 separation science, 16 filtration, 17 nanotechnology, 18 and drug delivery. 19 The effect of incorporating the chloromethyl moiety into the frustule of T. weissflogii on the characteristic architecture of the diatom was evaluated to ensure that there was no adverse effect of chemical modification.…”
mentioning
confidence: 99%